Aspects of individualisation in Dostoevsky’s novella The Double – the semiotic dynamics of definedness and undefinedness - Kroó, Katalin (Slavia Centralis, 2021)
The article investigates, from four points of view, the semantic processes in Dostoevsky’s work which shift the focus from the problem of social to semiotic individualisation. First, the protagonist’s social significance is interpreted in terms of the relationship between the whole (society) and its part (the individual), linked to the gain and loss of special character traits as semantic attributes. The second question lies in the peculiarity of the artistic language illuminating attribute distribution and deprivation. The third and fourth aspects of the examined problem concern the representation of imitative poetics (recurrent word-to-word repetitions, minor variations, the semanticisation of being similar to all the others) and the forms of its overcoming characterised by creative transformation. This sets new semiotic conditions for the designation of individuality (as personality and in semiosis).